An estimation-based solution to weak-grid-induced small-signal stability problems of power converters - Fang, Jingyang (2022)
The large-scale deployment of grid-tied power electronic converters in renewable generation, electric motor drives, and energy storage systems speeds up the global energy transition. However, the stability problems faced by power converters in weak grids, which feature large and variable grid impedances, stand as a serious challenge that has puzzled the power electronic community for more than 15 years. Existing solutions to weak-grid-induced small-signal stability problems modify system and/or control parameters so that stable operation is achieved under a certain condition. However, such solutions are problem and application-specific. Therefore, the solutions can hardly be generalized to various operating conditions or stability problems. As such, this article proposes an estimation-based solution that targets multiple weak-grid-induced small-signal stability problems, particularly for converters with grid-supportive services. The essence of the proposed solution lies in the accurate estimation of real grid information rather than the point-of-common-coupling information. For implementation, Kalman filters serve as an estimator. Subsequently, the estimated information is used to design controllers, such as voltage droop, that allow for stable power conversion. Finally, simulation and experimental results validate the effectiveness and generality of the proposed solution.